Mobile Computing 2009
DOI: 10.4018/978-1-60566-054-7.ch164
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of Camera Phones in Social Contexts

Abstract: This chapter reports on a qualitative study into people’s use of camera phones for social interaction in co-present settings. The study examined people’s behaviour and positive experiences (e.g., fun, enjoyment, or excitement) when camera phones were used in different spaces (public and private). It was found that camera phones influence social practices. Three distinct practices were observed: sharing a moment now, sharing a moment later, and using photos to initiate social interaction with strangers. The kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Other public spaces like pubs, restaurants, clubs, places of entertainment and leisure provide a different social context for camera phone activities, which is in line with our previous research reported elsewhere (Stelmaszewska et al, 2005(Stelmaszewska et al, , 2006. The data illustrates that people more often engage themselves in social interaction using camera phones during gatherings with friends and family, when going out with friends or during trips or excursions with friends (see Figures 1&2).…”
Section: Public Spacesupporting
confidence: 88%
“…Other public spaces like pubs, restaurants, clubs, places of entertainment and leisure provide a different social context for camera phone activities, which is in line with our previous research reported elsewhere (Stelmaszewska et al, 2005(Stelmaszewska et al, , 2006. The data illustrates that people more often engage themselves in social interaction using camera phones during gatherings with friends and family, when going out with friends or during trips or excursions with friends (see Figures 1&2).…”
Section: Public Spacesupporting
confidence: 88%
“…Other public spaces like pubs, restaurants, clubs, places of entertainment and leisure provided a different social context for sharing activities, which is in line with our previous research [23,24]. The data illustrates that people more often engage themselves in social interaction using camera phones during gatherings or parties with friends and family, when going out, or during excursions with friends.…”
Section: Public Placessupporting
confidence: 86%
“…The study presented here is an extension of our earlier work [23,24], which identified social uses and practices of camera phones users occurring in co-located settings. Three distinct practices were observed including 'sharing a moment now', 'sharing a moment later', and using photos to initiate social interaction with strangers.…”
Section: Description Of the Studymentioning
confidence: 99%
See 2 more Smart Citations